Іконописні центри старообрядців на Чернігово-Сіверщині у XVIII – XIX століттях - Миколайко, Т. (Сiверянський лiтопис, 2015)
Стаття присвячена центрам іконописання старообрядців на Чернігівщині. Особлива увага приділена іконописцям-старовірам Андрію та Василю Родіонцевим та Івану Алексєєву, які жили на Стародубщині. Статья посвящена центрам иконописи староверов на Черниговщине. Особое
внимание уделено иконописцам-староверам Андрею и Василию Родионцевым и Ивану
Алексееву, которые жили на Стародубщине. The article is dedicated to centers of iconography of oldbelievers in Chernihivschyna.
Particular attention is paid to the icon painters- oldbelievers Andrew and Vasili Rodiontsevym
who lived Starodubshchyna. The family was well-known painters in the region, as had his
own studio, performing order not only fellow believers, and for the orthodox, were engaged in
educational work, contributed to the opening of schools. Also, the article recall the names of icon
painters – Ivan Alexeyev, Adriyanov Trohym – this indicates that in the mid-XIXth icon painting
art in areas inhabited by oldbelievers developed and bring profi ts. Oldbelievers founded their
monasteries, built churches, and for their support, equip them with icon-painting workshop
engaged copper plastic art, religious embroidery and printing.